Correlation, Direct and Indirect Effect Studies of Different Characters on Seed Yield of Chickpea (Cicer arietinum L.) at Satna District of M.P. (International Journal of Food and Nutritional Sciences, 2022)
Twenty diverse cultivars of chickpea (Cicer arietinum L.) grown under Completely Randomized block design (CRBD) at AKS University, District- Satna, M.P. during Rabi season on November 2020. The eleven quantitative characters studied for the estimation of correlation and path coefficient analysis. The results was revealed that biological yield per plant (g.), number of secondary branches per plant, number of primary branches per plant, days to 50 percent flowering, days to maturity, plant height (cm.) and number of pods per plant showed high positive significant correlation with seed yield per plant at both genotypic and phenotypic levels, respectively. These features become the most important factors affecting chickpea seed yield. On the basis of path coefficient analysis showed that biological yield per plant (g.), days to maturity and number of pods per plant were important characters that could be taken into consideration for selection and improvement of seed yield in chickpea.